Plan de negocios para la creación de una hostería ecoturística en el sector Pansache Retamales en la ciudad de Latacunga. - Molina Álvarez, Douglas Fernando (2020)
Ecuador looks for that all tourism activities are sustentable and profitable in the future, within this framework, ecoturismo constituyes the most organized modality and with the greatest boom in recent years. The objective of this project is to determine the feasibility of creating an Ecotourism inn located in the Pansache Retamales páramo, in the Latacunga Canton. The research of this work is of great importance, since it is directed to the local territorial development of natural spaces. The main focus of the project is the conservation of nature and it brings great benefits. These include the mitigation of socio-environmental impacts, a fair redistribution of economic income and promoting the conservation of natural spaces, and the participation of local populations. An Economic and Financial study was carried out, where all the resources and factors to carry out the project were analyzed. As a first aspect, an initial investment of $ 360,392.23 was reflected. With regard to cash flow, the first year of execution was taken as a reference, in which a balance of $ 231693.01 will be obtained. On the balance sheet, accounts payable in the first year would be $ 160,260.02. Furthermore, after analyzing different financial indicators, the minimum acceptable rate of return (TMAR) is 36.57% and the investment recovery period will be achieved in 24 months at an internal rate of return (IRR) of 42%. Finally, the cost-benefit of the inn would be $ 1.75. Through this previous study and analysis, it can be seen that this project is viable and will generate profitability.